Archisport 2023, 27-29 May 2023: Super Sport Arena, Samarahan / Nur Atiqah Husaini ... [et al.] - Husaini, Nur Atiqah; Hamzah, Hanisah Aimi; Abdul Rahman, Abdul Ruqaim Ashraff; Aziz, Syazwani Aqmar (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The most anticipated annual AZV event, Archisport was held on the 27 to 28th of May 2023 at Super Sport Arena, Samarahan. This event was held by AZV high council, led by Constantine Embagos. The games competed included handball, futsal, dodge ball, and badminton, together with the design competition, Best Panji Award. This year’s champion title was hold by Ghedbull for 3 consecutive years. 2nd place was won by KaHulk while Bluetix comes in third place. Best Panji Award that was judged by the lecturers was won by ThunderShock. The event was participated by all AZV members and lecturers with passion and excitement wearing respective house representative colours.